Economic and cost-effectiveness analysis of the Community-Level Interventions for Pre-eclampsia (CLIP) trials in India, Pakistan and Mozambique - Bone, Jeffrey N (BMJ Glob Health, 2021)
BACKGROUND: The Community-Level Interventions for Pre-eclampsia (CLIP) trials (NCT01911494) in India, Pakistan and Mozambique (February 2014–2017) involved community engagement and task sharing with community health workers for triage and initial treatment of pregnancy hypertension. Maternal and perinatal mortality was less frequent among women who received ≥8 CLIP contacts. The aim of this analysis was to assess the incremental costs and cost-effectiveness of the CLIP intervention overall in comparison to standard of care, and by PIERS (Pre-eclampsia Integrated Estimate of RiSk) On the Move (POM) mobile health application visit frequency. METHODS: Included were all women enrolled in the three CLIP trials who had delivered with known outcomes by trial end. According to the number of POM-guided home contacts received (0, 1–3, 4–7, ≥8), costs were collected from annual budgets and spending receipts, with inclusion of family opportunity costs in Pakistan. A decision tree model was built to determine the cost-effectiveness of the intervention (vs usual care), based on the primary clinical endpoint of years of life lost (YLL) for mothers and infants. A probabilistic sensitivity analysis was used to assess uncertainty in the cost and clinical outcomes. RESULTS: The incremental per pregnancy cost of the intervention was US$12.66 (India), US$11.51 (Pakistan) and US$13.26 (Mozambique). As implemented, the intervention was not cost-effective due largely to minimal differences in YLL between arms. However, among women who received ≥8 CLIP contacts (four in Pakistan), the probability of health system and family (Pakistan) cost-effectiveness was ≥80% (all countries). CONCLUSION: The intervention was likely to be cost-effective for women receiving ≥8 contacts in Mozambique and India, and ≥4 in Pakistan, supporting WHO guidance on antenatal contact frequency. TRIAL REGISTRATION NUMBER: NCT01911494.